Chemistry: Serious Fun - American Chemical Society (1991)
In this video produced by the American Chemical Society, two actors from The Fresh Prince of Bel-Air, Alfonso Ribeiro and Tatyana Ali, prepare to attend a new semester at University of California, Los Angeles (UCLA). They use an on-campus chemistry lab to conduct a few experiments and discuss the value of chemistry. A voice over and interviews with scientists provide examples of chemistry in the news across many disciplines including marine biology, medicine, manufacturing, and forensic anthropology. Please note that this video contains footage of mummified human remains.
Keywords: Chemistry; Fresh prince of Bel Air (Television program); University of California, Los Angeles; Chemistry--Experiments; Science--Study and teaching